2010
DOI: 10.1039/b918583f
|View full text |Cite
|
Sign up to set email alerts
|

All-conjugated polyelectrolyteblock copolymers

Abstract: Novel, all-conjugated polyelectrolyte block copolymers of the rod-rod type can be generated in a ''grafting from'' scheme and exhibit a preferred tendency to self-assemble into layered aggregates both in solution and the solid state. Here, the rigid-rod structure of the individual, complex macromolecules favours the formation of low-curvature vesicular and lamellar aggregates. Our poly(9,9-dialkylfluorene)-b-poly [3-(6-ammoniumhexyl)thiophene] (PF2/6-b-P3TMAHT and PFO-b-P3TMAHT, where PF2/6 and PFO denote 2-(e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
52
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 30 publications
1
52
0
1
Order By: Relevance
“…Scherf et al . have notably shown that amphiphilic conjugated block copolymers containing both hydrophobic polyfluorene and hydrophilic cationic P3HT blocks ( P5,Br ) (Scheme ) exhibit solvent‐ and charge‐mediated self‐assembly . Judicious selection of the polarity of the solvent mixture allows modulation of the nanomorphology of the self‐assembled aggregates (e.g.…”
Section: Molecular Design and Performance Of Polythiophene Il Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Scherf et al . have notably shown that amphiphilic conjugated block copolymers containing both hydrophobic polyfluorene and hydrophilic cationic P3HT blocks ( P5,Br ) (Scheme ) exhibit solvent‐ and charge‐mediated self‐assembly . Judicious selection of the polarity of the solvent mixture allows modulation of the nanomorphology of the self‐assembled aggregates (e.g.…”
Section: Molecular Design and Performance Of Polythiophene Il Materialsmentioning
confidence: 99%
“…vesicles, rods etc. ), as well as their optical properties . Due to its solubility in polar solvents, this conjugated block copolyelectrolyte was used as an electron‐extracting layer in BHJ‐OPV cells and its performance was compared to that of the corresponding ionic polythiophene homopolymer ( P1,Br ) .…”
Section: Molecular Design and Performance Of Polythiophene Il Materialsmentioning
confidence: 99%
“…Ullrich Scherf* conjugation · light-emitting diodes · organic electronics · polymers · zwitterions Cationic conjugated polyelectrolytes (cationic CPEs) [1,2] as components of electronic devices came in the focus of interest since the first demonstration of their potential as effective electron-injecting layers in organic light-emitting diodes (OLEDs) and organic field-effect transistors (OFETs). A further application in "bulk heterojunction"-type organic solar cells (OSCs) has also been reported.…”
mentioning
confidence: 99%
“…2). 52 The hydrophilic nature of the polythiophene blocks leads to solvent-induced self-assembly in mixtures of selective and nonselective solvents, as observed for PF2/6-P3PHT in water-tetrahydrofuran (THF) or water-hexane 53 or PF2/6-b-P3TMAHT in water-THF 54 or water-MeOH. 55 Notably, the self-assembled structures generated in solution are transferred to the solidstate, such that PF2/6-b-P3TMAHT forms vesicular nanostructures in drop-cast lms prepared from low concentration methanolic solutions (0.03 mg mL À1 ) (Fig.…”
Section: Amphiphilic Cps: Blackberries Rods and Vesiclesmentioning
confidence: 99%
“…Films prepared from solutions at higher concentrations ($5 mg mL À1 ) lead to a denser coverage of the substrate and a transformation to solid state-like lms. 52 Atomic force microscopy (AFM) measurements reveal a transition from vesicular (region 1, Fig. 2a) to a lamellar morphology (region 3, Fig.…”
Section: Amphiphilic Cps: Blackberries Rods and Vesiclesmentioning
confidence: 99%